Pour une analyse contrastive des types de discours: I’exemple dufaire-part de décès en français et en espagnol - Drescher, Martina (Studia Romanica Posnaniensia, 2007)
This article undertakes the problems of contrastive analysis of discourse. The author discusses functioning of a definite, ossified structure on the example of French and Spanish obituaries. Similarities and differences in the social functioning of this type of texts are discussed in order to draw conclusions which also pertain to the theory of translation.